Polyimide-planarized, vertical-cavity surface emitting lasers with 17.0 GHz bandwith - Al-Omari, Ahmad N., author; Lear, Kevin L., author; IEEE, publisher (Colorado State University. Libraries, 2004)
High speed, oxide-confined, polyimide-planarized 850 nm vertical cavity surface emitting lasers (VCSELs) exhibit - 3dB modulation bandwidths up to 17.0 GHz. The devices are fabricated using a reproducible, simple process incorporating polyimide with good adhesion that does not require implantation or semi-insulating substrates to achieve low capacitance.
Keywords: optical polymers; p-n heterojunctions; optical modulation; adhesion; high-speed optical techniques; semiconductor device testing; semiconductor lasers; laser cavity resonators; optical fabrication; surface emitting lasers